Synthetic Fragments of Receptor for Advanced Glycation End Products Bind Beta-Amyloid 1–40 and Protect Primary Brain Cells From Beta-Amyloid Toxicity - Kamynina, Anna V.; Esteras, Noemi; Koroev, Dmitriy O.; Bobkova, Natalia V.; Balasanyants, Samson M.; Simonyan, Ruben A.; Avetisyan, Armine V.; Abramov, Andrey Y.; Volpina, Olga M. (Frontiers in Neuroscience, 2018)
Receptor for advanced glycation end products (RAGE) is involved in the pathogenesis of Alzheimer’s disease. We have previously revealed that RAGE fragment sequence (60-76) and its shortened analogues sequence (60-70) and (60-65) under intranasal insertion were able to restore memory and improve morphological and biochemical state of neurons in the brain of bulbectomized mice developing major AD features. In the current study, we have investigated the ability of RAGE peptide (60-76) and five shortened analogues to bind beta-amyloid (Аβ) 1-40 in an immunofluorescence test and show that all the RAGE fragments apart from one (sequence (65-76)) were able to bind Аβ in vitro. Moreover, we show that all RAGE fragments apart from the shortest one, (60-62), were able to protect neuronal primary cultures from amyloid toxicity, by preventing the caspase 3 activation induced by Аβ 1-42. We have compared the data obtained in the present research with the previously published data in the animal model of AD, and offer a probable mechanism of neuroprotection of the RAGE peptide.